Rethinking Population Policies from Family Planning to Population Management - Parajuli, Kewal Ram (Rupantaran: A Multidisciplinary Journal, 2020)
Population policy plays a significant role for the desired demographic and social outcome of a nation with aims of social welfare and progress. Basically, anti-natalist and pronatalist policies are adopted to influence fertility. Family planning programs and policies have been initiated with the aim of population management in Nepal but concentrated on fertility reduction in a later period, the continuation of such policies and rapid decreasing of fertility may create tribulation in future as developed countries with having a condition of depopulation. This paper attempts to analyze content related to fertility and family planning policies and activities thoroughly and the level, trend, and projection of fertility and family planning with the objective of finding future implications. Findings suggest that it should focused on population responsive policies, quality life of people, utilization of demographic dividends mostly on population management rather than anti-natalist population policy. Since a long time, Nepal has adopted the Anti-natalist population policy, which should be rethought for the sustainability of development and population management. Fertility, a major process of population increase, Basically, determined by many biological, sociocultural, economic, geographical factors, can’t increase as the nation’s desire and need. So, need to pay attention to prevent depopulation status.